2019
DOI: 10.1038/s41467-019-10349-z
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 S-acylation mediates DNA double-strand break repair at the inner nuclear membrane

Abstract: Rif1 is involved in telomere homeostasis, DNA replication timing, and DNA double-strand break (DSB) repair pathway choice from yeast to human. The molecular mechanisms that enable Rif1 to fulfill its diverse roles remain to be determined. Here, we demonstrate that Rif1 is S -acylated within its conserved N-terminal domain at cysteine residues C466 and C473 by the DHHC family palmitoyl acyltransferase Pfa4. Rif1 S- acylation facilitates the accumulation of Rif1 at D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 70 publications
1
34
0
Order By: Relevance
“…It is therefore plausible that TOP1ccs This is a particularly appealing model considering that TEX264 and SPRTN co-localise with nascent DNA at the nuclear envelope, where heterochromatin is tethered. Alternatively, TOP1ccs may be relocalised to the nuclear envelope, as has been demonstrated for other SUMOylated proteins and some types of DNA lesions [73][74][75] . It is perhaps less likely that TEX264 only operates on a specific subset of TOP1ccs, since numerous experimental approaches demonstrated that TEX264 and TDP1 act in the same pathway to repair endogenous TOP1ccs.…”
Section: Discussionmentioning
confidence: 81%
“…It is therefore plausible that TOP1ccs This is a particularly appealing model considering that TEX264 and SPRTN co-localise with nascent DNA at the nuclear envelope, where heterochromatin is tethered. Alternatively, TOP1ccs may be relocalised to the nuclear envelope, as has been demonstrated for other SUMOylated proteins and some types of DNA lesions [73][74][75] . It is perhaps less likely that TEX264 only operates on a specific subset of TOP1ccs, since numerous experimental approaches demonstrated that TEX264 and TDP1 act in the same pathway to repair endogenous TOP1ccs.…”
Section: Discussionmentioning
confidence: 81%
“…It is also required for immunoglobulin class-switch recombination during the germinal centre reaction for humoral antibody immunity (Di Virgilio et al, 2013). RIF1 is involved in telomere homeostasis and was recently found to be post-translationally S-acylated, identifying a novel posttranslational modification regulating DNA repair (Fontana et al, 2019). Post-translational deimination has hitherto not been described.…”
mentioning
confidence: 99%
“…It is noteworthy that a new study has been published linking RIF1 S-acylation by the DHHC family palmitoyl acyltransferase Pfa4 to DSB repair in yeast (Fontana et al, 2019). As no RIF1 orthologue exists in plants the PAT21 mediated process must be mechanistically different.…”
Section: Discussionmentioning
confidence: 99%